Improving Nutrition Among Infants And Toddlers During The Covid-19 Pandemic - Pratiwi Puji Lestari (UMBanjarmasin, 2021)
Introduction: Maternal and child malnutrition rates are also likely to increase as a result of COVID-19 and its impact on poverty, coverage of essential interventions, and access to appropriate nutritious food. The purpose of this community service activity is to help provide an understanding of the fulfillment and improvement of nutrition for infants and toddlers during the COVID-19 pandemic which is simple and can be done at home. Methods: The implementation of this activity includes the provision of material with the extension method. The contents of the material include providing education about the fulfillment and improvement of nutrition for infants and toddlers during the COVID-19 pandemic. The target of the implementation is mothers who have babies and toddlers and the community so that they can maintain maximum nutritional fulfillment for infants and toddlers despite all limitations during the COVID-19 pandemic. Results: After the implementation of counseling and education, it is hoped that mothers who have babies and toddlers can apply simple solutions that can be done at home and the community can also be a supporting factor in the fulfillment and improvement of nutrition for infants and toddlers during this covid 19 pandemic. Conclusion: Providing education about the fulfillment and improvement of nutrition for infants and toddlers during the COVID-19 pandemic as an effort to improve child feeding practices must be complemented by programs that increase household economic opportunities and access to food, especially during the COVID-19 pandemic.